Immunoglobulin patterns in keratoconus with particular reference to total and specific IgE levels. - Kemp, E. G. (1982)
A selection of sufferers from keratoconus and random controls were assessed in order to substantiate claims that there existed a significant incidence of patients with both keratoconus and a raised serum level of immunoglobulin E. The results appeared to confirm a high incidence of raised total serum IgE levels in patients with keratoconus and also indicated that the additional measurement of serum specific IgE was more sensitive than total IgE. In fact 59% of the patients with keratoconus in our study were identified as having significantly raised level of specific immunoglobulin E, and 52% were identifiable by measuring total immunoglobulin E. This compares favourably with a previous incidence in a keratoconus population of 47% with raised total immunoglobulin E. Our study avoids clinical estimation of known associated systemic manifestations of atopic disease, thereby reaffirming the correlation between raised serum levels of IgE and keratoconus as objectively as possible. This identification pattern may be useful in reviewing high-risk groups and aid in the earlier detection of the condition.